Comparison of Population and Feeding Ecology of Two Endangered Varanid Lizards of Bangladesh - Jaman, M. Firoj; Begun, M. Anisa; Mahmud, H. (Ecoprint: An International Journal of Ecology, 2016)
Available with fulltext. Key words: Population; Feeding ecology; Endangered varanids; Conservation Ecoprint An International Journal of Ecology Vol. 14, 2007 Page: 79-88 Uploaded date: 31 May, 2011